The International Congress of Psychology (ICP 2012): a brief analysis of the scientific programme. (September 2014) - Pillay, Anthony L; Pillay, Basil J; Duncan, Norman
South African Psychology has a unique history and stands out among its peers across the world. In the wake of its divided past and collusion with apartheid, its subsequent international 'rehabilitation' was capped by its successful hosting of the International Congress of Psychology (2012) during July 2012. This was the first such event on the African continent, and involved a mammoth organisational effort that spanned more than 6 years. This article briefly analyses the scientific programme within the context of the content areas and the countries represented. Some of the challenges faced by the Scientific Committee are also outlined, together with the strategies developed to manage these challenges.